Role of Hydrogen Transfer and Ionic Bonding on RR, SS and RS Medetomidine Conglomerates/Acids Stability: A Theoretical Study - Vahid Zarei; Nabi Javadi; Zainal Ghahramani; Hossein Fakhraian (Journal of Sciences, Islamic Republic of Iran)
This study focuses on RR, SS and RS medetomidine (MM) and inclusion of several achiral acids to distinguish which acid can help conglomerate formation instead of crystallizating racemic mixtures by defining the low-lying energy of their structures. Favorable orientation of acids was determined in interaction with the MM enantiomers after optimization. The most noticeable interactions include hydrogen transfer from acids to nitrogen (N) atom of the MM enantiomers, which was confirmed through quantum theory of atom in molecule (QTAIM) and natural bond orbital (NBO) analysis. In addition, nature and source of change of these bonds were investigated by determination of significant donor-acceptor interactions. The results revealed for obtaining RR and SS conglomerates; oxalic acid solvent provides the optimum stability. Furthermore, application of propanoic acid solvent should be neglected since MM crystallization is nonspontaneous with this solvent. Therefore, oxalic acid is the acid of choice for preferential conglomerate formation.